PENGARUH CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN BOOTH PADA EVENT VINKOO JAKARTA FEST 2025 DI MEDAN - Kartika Oktavia Pasaribu; Sarah Rouli Tambunan (Universitas Putera Batam, 2025)
Vinkoo Jakarta Fest is one of the fashion and culinary bazaars regularly held in Medan by Vinkoo Event Organizer since 2019. This event showcases products from various major cities in Indonesia and even abroad. In 2025, during the Chinese New Year celebrations, Vinkoo Jakarta Fest experienced significant growth with the number of booths increasing to 300 from the previous 120-160 booths, even featuring booths from Penang, which influenced purchasing decisions. However, there was a problem with the prices being set at the same level without considering strategic locations, which caused dissatisfaction among some tenants. Booth purchase decisions are greatly influenced by brand image and price, where a positive brand image can increase tenant confidence in the quality of the event, while a price that is in line with the benefits encourages tenant interest in participating. This study aims to examine how brand image and price influence booth purchase decisions at the Vinkoo Jakarta Fest event, both partially and simultaneously. This study uses a quantitative research method with data collection conducted through questionnaires. The data analysis technique used in this study is multiple regression analysis using the SPSS 26 data processing program with a total of 100 respondents. The results of this study indicate that brand image and price partially and simultaneously have a positive and significant effect on the decision to purchase a booth at the Vinkoo Jakarta Fest 2025 event in Medan. The results of the coefficient of determination (R2) test show that brand image and price can influence the decision to purchase a booth by 67.9%, with the remaining 32.1% influenced by other variables not examined in this study